1994
DOI: 10.1210/mend.8.10.7854358
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a novel orphan receptor (GCNF) expressed during germ cell development.

Abstract: We have cloned a novel member of the nuclear receptor superfamily that has been identified from complementary DNA libraries derived from mouse tissues using a low stringency cross hybridization strategy. The deduced protein sequence contains 495 amino acids and consists of the characteristic DNA-binding and ligand-binding domains of the nuclear receptor superfamily. The primary sequence of this new orphan is distinct from those of previously cloned members and subgroups. Analysis of the DNA-binding properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
108
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(115 citation statements)
references
References 1 publication
3
108
2
2
Order By: Relevance
“…It has been shown that GCNF is not only expressed in mouse and Xenopus embryos after the onset of gastrulation (14,(21)(22)(23)(24) but also in the gametogenic cells of adult vertebrates (3,4,11,18,(25)(26)(27). This expression pattern indicates that GCNF may play a role in gametogenesis and normal embryonic development during gastrulation.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…It has been shown that GCNF is not only expressed in mouse and Xenopus embryos after the onset of gastrulation (14,(21)(22)(23)(24) but also in the gametogenic cells of adult vertebrates (3,4,11,18,(25)(26)(27). This expression pattern indicates that GCNF may play a role in gametogenesis and normal embryonic development during gastrulation.…”
mentioning
confidence: 96%
“…GCNF was initially cloned by our laboratory using low stringency screening with a DNA binding domain (DBD) probe (3) and subsequently cloned by other laboratories and given other names, e.g. RTR (retinoid receptor-related testis-specific receptor (4)) and NCNF (neuronal cell nuclear factor (5)).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Fig 2, the molecular weight of the three different antigens spanned about ten folds i.e. the 55KD GCNF/RTR (germ cell nuclear factor/retinoid receptor-related testis-associated receptor) [8], [9] and a 38 KD newly discovered gene product Bin2a fragment expressed in E. Coli and the 5.9 KD ILP(insulin like peptide) [10] fragment expressed in yeast. The modified immunization method was paralleled with the tradi Fig 2. The SDS-PAGE pattern of the three purified proteins expressed from E.coli or yeast 1 # .…”
Section: Resultsmentioning
confidence: 99%